Modern environments and human health : revisiting the second epidemiological transition - Zuckerman, Molly K. (Hoboken, New Jersey : Wiley-Blackwell, 2014)
"Written in an engaging and jargon-free style by a team of international and interdisciplinary experts, Modern Environments and Human Health demonstrates by example how methods, theoretical approaches, and data from a wide range of disciplines can be used to resolve longstanding questions about the second epidemiological transition. The first book to address the subject from a multi-regional, comparative, and interdisciplinary perspective, Modern Environments and Human Health is a valuable resource for students and academics in biological anthropology, economics, history, public health, demography, and epidemiology"--
1 Introduction: Interdisciplinary Approaches to the Second Epidemiologic Transition / Molly K. Zuckerman -- Part 1 Causes of the Second Epidemiologic Transition -- 2 Infectious Disease in Philadelphia, 1690-1807: An Ecological Perspective / Gilda M. Anroman -- 3 Modeling the Second Epidemiologic Transition in London: Patterns of Mortality and Frailty during Industrialization / Sharon N. DeWitte -- 4 The Wider Background of the Second Transition in Europe: Information from Skeletal Material / Nikola Koepke -- 5 The Epidemiological Transition in Practice: Consumption, Phthisis, and TB in the 19th Century / Jeffrey K. Beemer -- Part 2 Epidemic Infectious Disease and the Second Epidemiologic Transition -- 6 Agent-Based Modeling and the Second Epidemiologic Transition / Carolyn Orbann, Jessica Dimka, Erin Miller and Lisa Sattenspiel -- 7 Does Exposure to Influenza Very Early in Life Affect Mortality Risk during a Subsequent Outbreak? The 1890 and 1918 Pandemics in Canada / Stacey Hallman and Alain Gagnon -- Part 3 Regional and Temporal Variation in the Second Epidemiologic Transition -- 8 The Second Epidemiologic Transition in Western Poland / Alicja Budnik -- 9 The Timing of the Second Epidemiologic Transition in Small US Towns and Cities: Evidence from Local Cemeteries / Lisa Sattenspiel and Rebecca S. Lander -- 10 Industrialization and the Changing Mortality Environment in an English Community during the Industrial Revolution / Peter M. Kitson -- Part 4 Marginalized and Underrepresented Communities in the Second Epidemiologic Transition -- 11 Short Women and Their Stagnating Growth: A Study of Biological Welfare and Inequality of Women in Postcolonial India / Aravinda Meera Guntupalli -- 12 Tracking the Second Epidemiologic Transition Using Bioarchaeological Data on Infant Morbidity and Mortality / Megan A. Perry -- 13 The Biological Effects of Urbanization and In-Migration on 19th-Century-Born African Americans and Euro-Americans of Low Socioeconomic Status: An Anthropological and Historical Approach / Carlina de la Cova -- Part 5 The Environment and the Second Epidemiologic Transition -- 14 Reassessing the Good and Bad of Modern Environments: Developing a More Comprehensive Approach to Health Trend Assessment / Lawrence M. Schell -- 15 Childhood Lead Exposure in the British Isles during the Industrial Revolution / Andrew Millard, Janet Montgomery, Mark Trickett, Julia Beaumont, Jane Evans, and Simon Chenery -- 16 The Hygiene Hypothesis and the Second Epidemiologic Transition / Molly K. Zuckerman and George J. Armelagos -- 17 Comparative Parasitological Perspectives on Epidemiologic Transitions: The Americas and Europe / Karl J. Reinhard and Elisa Pucu de Arajo -- Part 6 Epilogue -- 18 The Second Epidemiologic Transition, Adaptation, and the Evolutionary Paradigm / George J. Armelagos -- 19 The Second Epidemiologic Transition from an Epidemiologist's Perspective / Nancy L. Fleischer and Robert E. McKeown -- 20 Methodological Perspectives on the Second Epidemiologic Transition: Current and Future Research / Richard H. Steckel -- 21 The Current State of Knowledge on the Industrial Epidemiologic Transition: Where Do We Go from Here? / Timothy B. Gage.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Health transition; Epidemiology; Public health; Health Transition; Epidemiology -- History; Public Health; SOCIAL SCIENCE -- Anthropology -- Physical; Epidemiology; Health transition; Public health; Electronic books